2000
DOI: 10.1161/01.cir.101.8.862
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Menstrual Cycle on Sympathetic Activity, Baroreflex Sensitivity, and Vascular Transduction in Young Women

Abstract: Background-Our goal was to test sympathetic and cardiovagal baroreflex sensitivity and the transduction of sympathetic traffic into vascular resistance during the early follicular (EF) and midluteal (ML) phases of the menstrual cycle. Methods and Results-Sympathetic baroreflex sensitivity was assessed by lowering and raising blood pressure with intravenous bolus doses of sodium nitroprusside and phenylephrine. It was defined as the slope relating muscle sympathetic nerve activity (MSNA; determined by microneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
457
10
6

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 446 publications
(515 citation statements)
references
References 22 publications
42
457
10
6
Order By: Relevance
“…The present study did not notice any differences in the basal heart rate between the phases, which is similar to the findings of many other studies [17][18][19][20]. Similarly the insignificant differences in basal SBP and DBP values in this study were also in concordance with the findings of Sato et al, [11].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The present study did not notice any differences in the basal heart rate between the phases, which is similar to the findings of many other studies [17][18][19][20]. Similarly the insignificant differences in basal SBP and DBP values in this study were also in concordance with the findings of Sato et al, [11].…”
Section: Resultssupporting
confidence: 93%
“…Similarly the insignificant differences in basal SBP and DBP values in this study were also in concordance with the findings of Sato et al, [11]. Likewise a few studies have also reported similar results with respect to the mean arterial pressure [18,19,21]. This has been suggested to be because, the changes in HPA functioning over the course of the menstrual cycle are barely reflected in resting parameters and which may become prominent when the system is activated by a potent psychosocial stressor [16].…”
Section: Resultssupporting
confidence: 93%
“…47 In another report, increases of plasma levels of oestrogen and progesterone during the menstrual cycle were found to be associated with increased MSNA. 48 In that report, the baroreceptor reflex sensitivity controlling MSNA was found to be increased in relation to increased plasma levels of oestrogen and progesterone. 48 Although we did not examine the mechanisms underlying the observed gender-related differences, taking the above considerations together with previously published reports, 20,41,49,50 it is reasonable to raise the possibility that the lower sympathetic activity in women could be related to their greater sympatho-inhibitory baroreceptor reflexes than those in men.…”
Section: For Hypertensive Women (F-eht) and Men (M-eht) Normotensivementioning
confidence: 87%
“…[7][8][9][10] Several studies have shown that respiration contributes importantly to short-term modulation of sympathetic nerve traffic. [11][12][13][14][15] MSNA increases at end expiration and decreases to minimum levels at end inspiration. 11 Little is known about the contribution of spontaneous respiratory rate to baseline MSNA burst frequency.…”
mentioning
confidence: 95%